2012
DOI: 10.1002/lary.23539
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of frontal lobe sagging after endoscopic endonasal transcribriform resection of anterior skull base tumors: Is rigid structural reconstruction of the cranial base defect necessary?

Abstract: Rigid structural repair may not be necessary for ASB defect repair after endoscopic endonasal resection of the cribriform plate. Our technique for multilayer cranial base reconstruction appears to be satisfactory in preventing delayed frontal lobe sagging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…It is arguable if bony or rigid repair of the defect is required at all, however. Herniation appears to be minimal without rigid reconstruction at 10-months postoperatively, 13 although long-term assessment of this possibility is not yet available. From the available literature, rigid reconstruction may be more useful in larger defects, patients who have intracranial hypertension or intermittent pressure elevation as in obstructive sleep apnea, or those who may require future sinus surgery for continued disease (e.g., polyps or tumor).…”
Section: Discussionmentioning
confidence: 99%
“…It is arguable if bony or rigid repair of the defect is required at all, however. Herniation appears to be minimal without rigid reconstruction at 10-months postoperatively, 13 although long-term assessment of this possibility is not yet available. From the available literature, rigid reconstruction may be more useful in larger defects, patients who have intracranial hypertension or intermittent pressure elevation as in obstructive sleep apnea, or those who may require future sinus surgery for continued disease (e.g., polyps or tumor).…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] With the triple-layer repair, we have found that rigid structural reconstruction of the anterior cranial base (with mesh, Medpor, or bone) is not necessary to prevent frontal lobe sagging or encephalocele formation. 48 …”
Section: Skull Base Reconstructionmentioning
confidence: 97%
“…It appears that even in large defects, rigid skull base reconstruction is not required to prevent subsequent cerebral herniation through the defect [13]. However, in scenarios where repeat surgery may be required in the future (e.g.…”
Section: Rigid (Bone/cartilage) Versus Nonrigidmentioning
confidence: 99%